(untitled) - Huaca Banegas, Jamela Elizabeth (2017)
The study in question considers an assertive style of communication on the part of the parental system in order to establish limits for the grade 1 students of the class ―Segundo B‖ at ―18 de noviembre‖ elementary school in Loja, the capital city of the province with the same name in Ecuador. This research is conducted with the general objective of promoting assertive communication as a means of establishing limits in the parental system of this class. To this end the study employed the following methods: inductive, scientific and statistical analysis to help propose solutions to the problem through a systematic process and in this way find alternative solutions and get results. The techniques used were direct observation, this was also used to observe the children, surveys and tests; these tools were used with the parents of the school children and provided information about the topic in question. The work was done with different variables in the study of assertive communication and the limits in the parental system with the goal of providing an alternative solution with regards to the study. The population under consideration was made up of 35 children and 35 of their parents. The alternative that was put into practice as a potential solution, at least in part, to the issue was the use of educational workshops. The promise of this strategy and it’s efficacy as a proposal. In view of these results it was concluded that the study had a clear theoretical basis and that the research highlighted the challenges inherent in this topic as well as the positive results in terms of raising awareness on the part of the parents on the importance, efficacy and variety of different strategies for employing assertive communication in the household.